PEMELIHARAAN HUBUNGAN INTERPERSONAL ANTARA PELATIH DAN ATLET DALAM MEMOTIVASI UNTUK BERPRESTASI PADA ATLET PPLP JAWA TENGAH - Muhammad Raditya Dwi Adhyatma; Triyono Lukmantoro; Joyo Nur Suryanto Gono (Interaksi Online, 2023)
The interpersonal relationship between athletes and coaches is unique due to the high willingness of both parties to succeed, which requires a good interpersonal relationship. This research aims to determine how the interpersonal relationship between the coach and athletes can influence the motivation of athletes from the Central Java PPLP Swimming team to develop and achieve excellence, as well as identify potential obstacles that may arise in this relationship. The research method used in this study is qualitative descriptive research. The results of this study show that the interpersonal relationship between the coach and athletes of the Central Java PPLP Swimming team is quite good based on the four analyzed aspects: positivity, openness, assurances, and sharing tasks. However, there are issues that arise between the coach and athletes in terms of positivity and openness. The findings of this research are in line with the equity theory, which explains that interpersonal relationships should be based on the equality of effort and rewards so that both athletes and coaches feel satisfied and can work together effectively to achieve their goals. Therefore, both the coach and athletes have a responsibility to address their shortcomings and strengthen the interpersonal relationship.